RAPID, METHOD FOR DETERMINATION OF METFORMIN AND CANAGLIFLOZIN IN PLASMA BY LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETER, APPLICATION TO BIOEQUIVALENCE STUDY - RAO PURAM, SAMBASIVA; G, NITHYA; RAO NB, SUBBA; BATHEJA, RAMAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to develop and validate a rapid selective bioanalytical method for the simultaneous determination of metformin and canagliflozin in plasma by liquid chromatography-tandem mass spectrometer (LC-MS/MS) to facilitate bioequivalence study sample analysis. Stock solutions and spiking solutions were prepared accurately in methanol and 80% methanol in water, respectively. Methods: Chromatography monitored using Analyst 1.6.2 software. Method was found selective, no matrix effect, reproducible and consistent recovery, accuracy, precision, and stable in aqueous as well as extracted/matrix samples. Method found linear over the range 10–2000 ng/ml for metformin and 30–6000 ng/ml for canagliflozin. The method is successfully applied to analyze samples collected in a bioequivalence study after administration of metformin/canagliflozin 1000/150 mg to 24 healthy male volunteers. Results: Extraction was carried out using a simple solid phase extraction using mobile phase elution. 5 μl sample delivered as injection volume in 1.000 ml/min isocratic mobile phase flow on turbo ion electron spray technique for positive mode on API 4000 MS. Discussion: Chromatography achieved within 3 min using a mobile phase containing acetonitrile and 10 mM ammonium formate buffer in a ratio of 70:30 on chromolith C18 analytical column. Q1/Q3 are 130.1/70.1, 136.3/77.1, 462.2/267.2 (with ammonium adduct), and 466.4/267.1 for metformin, metformin D6, canagliflozin, and canagliflozin D4, respectively. Conclusion: Rapid, sensitive method for the simultaneous estimation of metformin and canagliflozin in plasma by LC-MS/MS is successfully developed, validated and applied to analyze 960 unknown samples of a bioequivalence study. Incurred sample reanalysis was revealed great reproducibility.